Biomarkers and risk assessment : concepts and principles (Geneva, 1993)
A guide to the concepts and principles governing the use of biomarkers to assess the risks to human health posed by exposure to chemical agents. Emphasis is placed on criteria for the selection and validation of appropriate biomark-ers of exposure, of toxic effect, and of susceptibility in either individuals or sub-populations. The book also explains how the use of validated biomarkers to monitor exposed populations can provide the basis for early public health interventions.